Internalized Stigma in Acne Vulgaris Patients and Relationship with Quality of Life, Disease Severity - Tosun, Nurperihan; Tosun, Mustafa; Digis, Mahir; Younis, Mustafa (Mdpi, 2025)
Background/Objectives: Acne vulgaris (AV), a common dermatological condition in adolescence, has been widely recognized not only for its physical impact but also for its significant psychological and social consequences, particularly the internalization of stigma. This study specifically aimed to evaluate the state of internalized stigma in adolescents with AV and its relationship with quality of life and disease severity. Additionally, we sought to identify and assess the factors associated with internalized stigma. Methods: A total of 179 patients with AV were included in this cross-sectional observational study. We employed a convenience sampling strategy. The Internalized Stigma Scale (ISS) was used to assess patients' stigma. The Acne Quality of Life Scale (AQLS) and the Dermatology Life Quality Index (DLQI) were used to assess patients' quality of life. The Global Acne Grading System (GAGS) was used to assess disease severity. Results: Cronbach's alpha coefficient for the ISS was determined to be 0.79. In our study, the mean total ISS scores for patients with AV were notably high. The ISS was significantly positively correlated with the AQLS score (r = 0.653, p < 0.001), DLQI score (r = 0.487, p < 0.001), and GAGS score (r = 0.257, p = 0.006). Linear regression analysis was performed to predict the ISS variable. Accordingly, the AQLS positively and significantly predicts (beta = 0.521, p < 0.001). Conclusions: AVs often experience high levels of stigma. Internalized stigma is strongly associated with reduced quality of life and increased disease severity. Moreover, the AQLS significantly affects stigma.
Keywords: internalized stigma; acne vulgaris; quality of life; disease severity